2005
DOI: 10.1097/00075197-200503000-00017
|View full text |Cite
|
Sign up to set email alerts
|

The role of the dietitian in the intensive care unit

Abstract: The scope of practice of intensive care dietitians defines them as clinicians, educators and researchers. Their skill set is a unique and vital component of the intensivist-led multidisciplinary intensive care unit team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Darawad, et al and others also reported that healthcare professionals commonly understand the significance of nutrition in managing patients, but their knowledge is inadequate. 13,16,17 Even in hospitals with competent staff and trained professionals, nutritional support was sporadic and hampered by inconsistency and miscommunication.…”
Section: Guidelinesmentioning
confidence: 99%
See 3 more Smart Citations
“…Darawad, et al and others also reported that healthcare professionals commonly understand the significance of nutrition in managing patients, but their knowledge is inadequate. 13,16,17 Even in hospitals with competent staff and trained professionals, nutritional support was sporadic and hampered by inconsistency and miscommunication.…”
Section: Guidelinesmentioning
confidence: 99%
“…One tool often utilized in this calculation is indirect calorimetry. 13,15 Even with this tool, it is challenging to determine the exact caloric needs of each patient.…”
Section: Total Caloric Needs and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…3 This interdisciplinary team approach has been shown to reduce cost and improve patient outcomes, and the RD is a key resource in various aspects of nutrition support therapy, including determinations of route and timing. 23 Skipper 24 suggests that the dietetics profession consider the model of the profession of advanced practice nursing, which is a definitive model for progressive clinical practice. For the advanced level practice RD in nutrition support, this model could include activities such as management of insulin therapy, catheter and device care, etc.…”
mentioning
confidence: 99%